Effects of Partially Replacing the Commercial Soybean Meal, With A Soaked and Boiled Raw Full-Fat Soybean in Broiler Diets - Erdaw, Mammo Mengesha; Guteta, Alemayehu (Turkish Journal of Agriculture - Food Science and Technology, 2024)
The aim of this study was to investigate the effects of partially replacing the commercial soybean meal (SBM) with a home-treated, locally produced raw-full fat soybean (RFFSB) in the diets of broilers. A 3×2×2+1 factorial arrangement was used to conduct this feeding trial. A test ingredient (RFFSB) was differently soaked (0, 6 or 12 hrs), drained, boiled (25 or 35 min) and sundried. Following this, it was hammered to pass through a 0.2-mm sieve, then 12 experimental diets were formulated, replacing the SBM by such a home-treated-RFFSB at 50 or 75%. The control diet didn’t contain any RFFSBN. Totally 13 experimental diets were prepared and every treatment was replicated 3 times and 10 chicks per replicate. The results revealed that replacing the commercial SBM by a treated RFFSB had no significant interaction effects on any measured parameter. However, soaking and then boiling it (RFFSB) had significant (P<0.05) interaction effect on the BWTG (1-13d and 14-28d). When increasing the soaking time, the FI (feed intake), BWTG (body weight gain) and feed efficiency were significantly (P<0.05) decreased. When increasing the boiling duration, both FI and feed efficiency (14-28d) were improved. But, when increasing the replacement rate of RFFSB, the feed efficiency was deteriorated. Broilers fed on both control and diets, containing a non-soaked RFFSB had higher (P<0.05) BWTG (1-13d). Birds fed on diets containing RFFSB that was soaked for the longest period (12 hrs) had significantly lower BWTG. Birds fed on diets, containing prolonged boiling duration had significantly (P<0.05) higher BWTG and feed efficiency. There was no interaction (P> 0.05) effect on both carcass yield and cut-products. Neither increasing a boiling time nor a replacement rate had (P<0.05) any influence on the WT (weight) of the carcass. Birds on both control and on non-soaked RFFSB diets had better WT of carcass products. There was no interaction (P>0.05) effect on organ developments. However, increasing the soaking-duration significantly (P<0.05) reduced the organ developments. Therefore, it is concluded that commercial SBM can be replaced by a non-soaked, but boiled raw soybean in diets of broilers.